Associations between area-level arsenic exposure and adverse birth outcomes: An Echo-wide cohort analysis - Jonathan V. Lewis; Emily A. Knapp; Shivani Bakre; Aisha S. Dickerson; Theresa M. Bastain; Casper Bendixsen; Deborah H. Bennett; Carlos A. Camargo; Andrea E. Cassidy-Bushrow; Elena Colicino; Viren D’Sa; Dana Dabelea; et al. (Environmental Research, 2023)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Gene expression accurately distinguishes liver metastases of small bowel and pancreas neuroendocrine tumors - Scott K. Sherman; Jessica E. Maxwell; Jennifer C. Carr; Donghong Wang; Andrew M. Bellizzi; M. Sue O’Dorisio; Thomas M. O’Dorisio; James R. Howe (Clinical & Experimental Metastasis, 2014)

How spatially coherent and statistically robust are temporal changes in extreme precipitation in the contiguous USA? - S. C. Pryor; J. A. Howe; K. E. Kunkel (International Journal of Climatology, 2009)
Century‐long precipitation records from stations in the contiguous USA indicate an increased frequency of rainy days over the past century and some evolution in the probability distributions of precipitation amount. Temporal trends in eight metrics of the precipitation climate are of similar magnitude and sign regardless of whether they are derived from bootstrapping of regression residuals or using the Kendall's tau statistic, though the bootstrap technique generally resolved a larger number of ‘significant’ trends. There is substantial variability in terms of the magnitude, significance and sign of the linear trends with specific metrics, and they are sensitive to recording bias of light precipitation events in the early part of the 20th century. The majority of stations that exhibit significant linear trends show evidence of increases in the intensity of events above the 95th percentile. The resolved trends tend to have a larger magnitude at the end of the century. Spatial variability as manifest in the spatial autocorrelation in the interannual variability and trends in extreme metrics is manifest at a range of scales, but in general the correlation between stations is significant only for separation of distances of a few tens of kilometres. The largest trends towards increased annual total precipitation, number of rainy days and intense precipitation (e.g. fraction of precipitation derived from events in excess of the 90th percentile value) are focussed on the Central Plains/northwestern Midwest. Copyright © 2008 Royal Meteorological Society

Photopigment spectral absorbance of Lake Malaŵi cichlids - R. Jordan; K. Kellogg; D. Howe; F. Juanes; J. Stauffer; E. Loew (Journal of Fish Biology, 2006)
To predict spectral sensitivity, microspectrophotometry (MSP) was used to measure absorbance of photoreceptor cells from 15 species of Lake Malaŵi cichlids. Each fish had one rod and at least three cone pigments. UV‐sensitive pigments were common, but spectral sensitivity did not clearly correlate with feeding mode or habitat.

Ultraviolet reflectivity in three species of Lake Malaŵi rock‐dwelling cichlids - R. Jordan; K. Kellogg; F. Juanes; D. Howe; J. Staufferals; E. Loew; G. Losey (Journal of Fish Biology, 2004)
The body colouration extending into ultraviolet wavelengths in three species of Lake Malaŵi rock‐dwelling cichlids, Metriaclima zebra , Metriaclima benetos and Metriaclima barlowi was quantified. All three species were ultraviolet reflective with interspecific differences in reflectivity. In addition, individuals were able to behaviourally mediate their reflectivity.

Highly variable SSR markers in Douglas-fir: Mendelian inheritance and map locations - G. T. Slavov; G. T. Howe; I. Yakovlev; K. J. Edwards; K. V. Krutovskii; G. A. Tuskan; J. E. Carlson; S. H. Strauss; W. T. Adams (Theoretical and Applied Genetics, 2004)

Annual cycles of phytoplankton community-structure and bloom dynamics in the Neuse River Estuary, North Carolina - J. L. Pinckney; H. W. Paerl; M. B. Harrington; K. E. Howe (Marine Biology, 1998)

A recombinant fowlpox virus that expresses the VP2 antigen of infectious bursal disease virus induces protection against mortality caused by the virus - C. D. Bayliss; R. W. Peters; Jane K. A. Cook; R. L. Reece; K. Howes; M. M. Binns; M. E. G. Boursnell (Archives of Virology, 1991)